Can we look bee colonies as biological indicators of forest ecosystem? A comparative study of the occurrence of bee colonies in some protected areas of Rajasthan, India - Sagar, Bhardwaj Gobind; Singh, Hemant; Gupta, Mohit; Dahiya, Savita; Singh, Sunil; Sharma, Sudarshan; Kumar, Anand; Singh, Janeshwar (Indian Forester, 2022)
Survey of colonies of Apis dorsata was conducted in five reserves, including Keoladeo national park (KNP), Jhalana leopard reserve (JLR), Sariska tiger reserve (STR), Sitamata wildlife sanctuary (SWS), Bassi wildlife sanctuary (BWS), located in semi-arid landscape of Rajasthan. Bee colonies were observed mostly on medium to large sized trees in the study areas demonstrating the role of size of trees irrespective of species type. The observation of high density of bee colonies in KNP (d = 7.1 colonies/km²) can be attributed to low intensity of anthropogenic pressures that is evident from low PIPUA (p' = 1.68). In contrast observation of low density of bee colonies in STR and SWS (d = 0.2, 0.1 colonies/km²) can be attributed to high anthropogenic interferences which is evident from the observation of high PIPUA (p' = 8.04, 8.08 respectively). Thus, the bee colonies can be considered as biological indicator of forest ecosystem.